STUDY OF FOREARC BASIN IN SUMATRA ASEISMIC ZONE BY RAY-TRACING TOMOGRAPHY - SUKMA PUTRA (NIM : 20213013), ADAM
Here, we present our results from traveltime tomography applied on seismic refraction data recorded in Sumatra forearc Basin. Our objective is to characterize and reveal the Low Velocity Zone (LVZ) linked to the presence of the fluid and gas which possibly exist underneath the forearc Basin of Sumatra fault. We obtain the data set acquired by CGGVeritas in 2009 with 15 km of streamers, the longest streamer ever used. First, we conducted the velocity analysis from seismic reflection data followed by Ray Based-Traveltime Tomography (Ray Tracing tomography) (RTT) of refracted phases. the first inversion has been done by performing RTT using initial velocity profile of Huot (2013) then we modified the profile in order to increase the accuracy. final velocity result of the tomography shows us the LVZ underneath the push-up ridge in between the continental crust and the accretionary wedge. The presence of a low velocity zone could be due to the presence of fluid or gas.